2019
DOI: 10.1186/s13756-019-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Airborne fungal spores and invasive aspergillosis in hematologic units in a tertiary hospital during construction: a prospective cohort study

Abstract: Background Invasive aspergillosis (IA) is an opportunistic fungal infection that mostly occurs in immunocompromised patients, such as those having hematologic malignancy or receiving hematopoietic stem cell transplantation. Inhalation of Aspergillus spores is the main transmission route of IA in immunocompromised patients. Construction work in hospitals is a risk factor for environmental fungal contamination. We measured airborne fungal contamination and the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Our results showed an even higher frequency of cryptic species in environmental isolates, as corroborated by Simpson index value. As already shown in several studies [ 48 , 49 , 50 , 51 ], the environment represents the major source of Aspergillus isolates causing infections. Exposure to Aspergillus may occur at home, in agricultural/animal production, at the workplace, and during periods of hospitalization, among others.…”
Section: Discussionmentioning
confidence: 89%
“…Our results showed an even higher frequency of cryptic species in environmental isolates, as corroborated by Simpson index value. As already shown in several studies [ 48 , 49 , 50 , 51 ], the environment represents the major source of Aspergillus isolates causing infections. Exposure to Aspergillus may occur at home, in agricultural/animal production, at the workplace, and during periods of hospitalization, among others.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the outcomes of 2018 were compared to the quality of air at the sewage treatment plant in order to indicate the likely origin of the species. Filamentous fungi of the genus Aspergillus , Cladosporium, and Mucor and yeast-like fungi, for example, Candida, were detected in domestic human and animal sewage [ 35 , 36 , 37 , 38 ]. Michałkiewicz et al found that the majority of yeast-like fungi isolated from the air of the four wastewater treatment plants was Candida [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are not cleaned as often as the frequent contact surfaces [33]. However, they may sustain the microbes and can result in transmission by accidental contact, or by indoor air contamination during cleaning, construction, and renovation operations [34,35]. Such air contamination is less likely, and if it happens, can cause respiratory and surgical site wound infections in susceptible patients [27].…”
Section: Medium Touchmentioning
confidence: 99%